Russian Growing Influence in the Black Sea: Implications on Regional Security - Sabah, Kalsoom; Ullah, Kaleem; Khattak, Umama (ACADEMIA International Journal for Social Sciences, 2025)
After world war 2, a cold war between west and USSR started and ended with the disintegration of USSR into multiple independent states. This event led to a major geopolitical shift and reshaped the politics of the region. Black sea is located at the center of these states, it is a gateway of Eastern Europe to global sea lanes of communication and Mediterranean and it links Europe to Caucasus and Middle East. Russia considers Black sea as significant for its geopolitical and strategic goals, driven by Moscow’s perception of the region as crucial for its geostrategic objectives, presents a pressing challenge to regional security. The strategic significance of the Black Sea for the Russian federation raises concerns about potential repercussions as the nation pursues and safeguards its interests in the area. This complex situation raises concerns regarding military activities, geopolitical tensions, economic ramifications, and the potential for cross-border ramifications. The research highlights the various threats posed to regional security, shedding light challenges that have resulted as a consequence of evolving geopolitical landscapes in the Black Sea. Russia uses multifaceted approaches like military buildup, economic and diplomatic ties, political maneuvering, historical and cultural affiliations to achieve its interest and goals in the region. Research is divided into five chapters; first chapter provides synopsis of whole research conducted. In chapter two, the theoretical framework about the Russia endeavors in the region along with the implications on the region are discussed in the research along with the literature review is presented. The Chapter three gives the methodological approach of the research conducted giving detail about the material and approach used in the research. Chapter four of the research presents the details of findings and data, it examines the geopolitical and geostrategic goals of Russia in the Black sea, key mechanisms and strategies employed by Russia to grow its influence in the region along with its implications on the regional security. The last chapter of the research concludes the whole research.